Strategi Promosi Virtual Tour oleh KEMENPAREKRAF dan Traveloka Melalui Media Sosial Instagram - Moniaga, Natasha Erinda Putri; Ariwangsa, I Made Bayu; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA, 2022)
Pandemic caused by the Covid-19 virus paralyzed many sectors of activities in the community, including the tourism sector so that a strategy to promote tourism through virtual travel is needed. Traveling is difficult to do because of restrictions on activities carried out by the government, in order to reduce the rate of spread of this disease. People are forced to be quiet and work indoors, although some types of jobs are still allowed to move. Staying indoors and not being able to travel can certainly cause its own stress. On social media later, one of them, appeared various services that offer virtual tourism services, including those held by the Ministry of Tourism. This service invites participants to travel together through various online media, provided by a guide who will lead the course of the activity, just as is commonly done in the real world. This promotional strategy is expected to be able to; 1) increase tourist interest in virtual traveling, 2) the creation of digital tourism for the future, 3) ease of travel, 4) Emphasis on travel costs, 5) the sustainability of virtual traveling. The purpose of this study was to look at the promotional strategies carried out by Kemenparekraf and Traveloka, as well as review the effectiveness of the virtual travel service. To be able to answer the problem, quantitative research methods are used by distributing questionnaires to a number of eighty students. The results of this study can be used to assess the effectiveness of virtual tourism and its possible future development. Keywords : Virtual Travelling, Promotional Strategies, Social Media